Stereo-Preference in the Degradation of the Erythro and Threo Isomers of β‐O‐4‐Type Lignin Model Compounds in Oxidation Processes: Part 1: In the Reaction with Active Oxygen Species Under Oxygen Delignification Conditions. (3rd July 2016) - Posoknistakul, Pattaraporn; Akiyama, Takuya; Yokoyama, Tomoya; Matsumoto, Yuji
Abstract : We examined whether or not active oxygen species (AOS) stereo-preferentially attack the erythro or threo isomer of non-phenolic β - O -4 -type lignin model compounds under oxygen delignification conditions. When AOS were generated in situ by the reaction between O2 and co-existing 4-hydroxy-3-methoxybenzyl alcohol (vanillyl alcohol), the obtained results could be explained on the basis of the hypothesis that an electrostatic repulsion exists between the negatively charged oxyl anion radical and the side-chain of the erythro isomer carrying the α -alkoxide anion. This repulsion prevents the reaction between the two species and, consequently, the erythro isomer is degraded less than the threo isomer. When 2, 4, 6-trimethylphenol (TMPh) was used to generate AOS, the reverse stereo-preference was observed. This reversal could be attributed to the neutral nature of a peroxyl radical that is an important AOS in the TMPh system and can attack the side-chain of the erythro isomer carrying the negatively charged α -alkoxide anion.